Answer:
The answer is 6/49, I hope this helps.
Answer:
your answer will be D
Step-by-step explanation:
look at the graph and find a corner by the black line there is a corner by -2 and positive 2
Answer:
x=-3
Step-by-step explanation:
If x=-3, then
x³+x²-2x+12=-27+9+6+12=-27+27=0
If this is true, then x+3 is a factor. So:
x³+x²-2x+12/x+3=x²-2x+4
So the factors of x³+x²-2x+12 are:
(x+3)(x²-2x+4)
((x²-2x+4) has no real roots)........
Answer:
m=14
n=32
p=64
Step-by-step explanation:
B=M, so 154=11m
m=154/11
m=14
E=P, so 118=n+86
n=118-86
n=32
A=L, so 116=180-p
p=180-116
p=64
Answer:
A. The variable x in the first equation has a coefficient of one so there will be fewer steps to the solution.
Step-by-step explanation:
Given
![Equation\ 1: x - 3y = 1](https://tex.z-dn.net/?f=Equation%5C%201%3A%20x%20-%203y%20%3D%201)
![Equation\ 2: 7x + 2y = 7](https://tex.z-dn.net/?f=Equation%5C%202%3A%207x%20%2B%202y%20%3D%207)
Required
Efficient way of solving the equations
<em>The efficient way of solving this problem is by solving for x in the first equation because it has a coefficient of 1;</em>
The evidence is shown as follows;
<em>Make x the subject of formula in equation 1</em>
![x = 1 + 3y](https://tex.z-dn.net/?f=x%20%3D%201%20%2B%203y)
<em>Substitute 1 + 3y for x in equation 2</em>
![7x + 2y = 7](https://tex.z-dn.net/?f=7x%20%2B%202y%20%3D%207)
![7(1 + 3y) + 2y = 7](https://tex.z-dn.net/?f=7%281%20%2B%203y%29%20%2B%202y%20%3D%207)
<em>Open bracket</em>
![7 + 21y + 2y = 7](https://tex.z-dn.net/?f=7%20%2B%2021y%20%2B%202y%20%3D%207)
![7 + 23y =7](https://tex.z-dn.net/?f=7%20%2B%2023y%20%3D7)
<em>Make y the subject of formula</em>
![23y = 7 - 7](https://tex.z-dn.net/?f=23y%20%3D%207%20-%207)
![23y = 0](https://tex.z-dn.net/?f=23y%20%3D%200)
<em>Divide both sides by 23</em>
![\frac{23y}{23} = \frac{0}{23}](https://tex.z-dn.net/?f=%5Cfrac%7B23y%7D%7B23%7D%20%3D%20%5Cfrac%7B0%7D%7B23%7D)
![y = 0](https://tex.z-dn.net/?f=y%20%3D%200)
Recall that x = 1 + 3y
<em>Substitute 0 for y in the above expression</em>
![x = 1 + 3(0)](https://tex.z-dn.net/?f=x%20%3D%201%20%2B%203%280%29)
![x = 1 + 0](https://tex.z-dn.net/?f=x%20%3D%201%20%2B%200)
![x = 1](https://tex.z-dn.net/?f=x%20%3D%201)
Solving for y in the second equation will take more steps